POSTOPERATIVE PAIN MANAGEMENT IN A PRIVATE HOSPITAL IN CENTRAL INDONESIA - Frily Olivia Leleh; Nikita Maola; Alice Yvonne Yovita Pangemanan; Tirolyn Panjaitan (Nursing Current: Jurnal Keperawatan, 2022)
Postoperative patients' most prevalent and expected complaint is pain. The pain might interfere with patients' daily activities and, if left untreated, can lead to neurogenic shock. The involvement of nurses in pain management for postoperative patients is critical, both independently and collaboratively, via pharmaceutical and non-pharmacological therapy. The goal of this study was to determine how pain was managed in postoperative patients in a private hospital in Central Indonesia. In this study, a quantitative descriptive method was applied, and a total of 137 documents were gathered from January to March 2018 utilizing a total sample technique in May 2018. According to the findings of the study, 114 patients (83.2 %) reported mild pain, 17 patients (12.4 %) reported moderate pain, 6 patients (4.4 %) reported no discomfort, and no one reported severe pain. It also revealed that 72 patients (53%) received a combination of pharmacology and non-pharmacology pain therapy, 54 patients (39%) received pharmacological pain management, and the remaining four patients (3%) received nonpharmacological pain management. Nurses were found to use a combination of both therapies more than either pharmacological or nonpharmacological treatment alone.